Lethrinus ravus, a new species of emperor fish (Perciformes: Lethrinidae) from the western Pacific and eastern Indian oceans - Carpenter, Kent E.; Randall, John E. (Zootaxa, 2003)
Lethrinus ravus is described from localities in the western Pacific. Photographic records also confirm its presence in Western Australia. It co-occurs with and is morphologically very similar to L. semicinctus but differs consistently in color pattern and average number of scales in the supratemporal patch of scales. Lethrinus semicinctus has a dark oblong blotch under the soft dorsal fin straddling the lateral line and a cluster of darkened scales in front of the base of the pectoral fin while L. ravus lacks these markings. Lethrinus ravus has black-lined scales that form rows above the lateral line and are scattered below the lateral line; this pattern is absent in L. semicinctus. Lethrinus ravus also frequently has more scales in the supratemporal patch than L. semicinctus. Both L. semicinctus and L. ravus have a cluster of scales with black lines above the base of the pectoral fin. This shared specialization is unique within Lethrinus and is evidence for a sister-species relationship.